Criticality as Ideological Becoming: Developing English Teachers for Critical Pedagogy in Nepal. Issue 2 (3rd July 2017) - Sharma, Bal Krishna; Phyak, Prem
Abstract : This article presents a discussion of how criticality is constructed and implemented for English as a foreign language (EFL) teacher development in Nepal. The authors draw on Freire's (1970) notion of conscientization to discuss how Nepali EFL teachers develop critical awareness in incorporating local sociopolitical issues in their lessons. Building on Bakhtin's (1981) concept of ideological becoming, they analyze these teachers' ideological becoming in adopting a critical approach to their pedagogical practices. The authors discuss the process of critical materials development, a subsequent professional development workshop, and a follow-up dialogue with teachers to show how critical awareness emerges from engaging teachers in understanding ideological tensions between dominant and alternative discourses of teachers' professional development. They interpret teachers' ideological tensions and their new consciousness in terms of their emerging sense of agency and a commitment toward a possible social transformation. The authors also argue that ideological conflicts and tensions in teachers' knowledge, teaching philosophies, and practices are a starting point for a transformative teacher development and they should be a core part of second language teacher education and professional development for second language teachers.